IMPLEMENTASI METODE PROBLEM POSING DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMPI SABILUL MUHTADIN BEKASI - Pandu Ibnu Nurrahman; Siti Asiah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
This research was conducted to find out how the implementation of the problem posing method in improving learning activities in Bekasi and to find out the supporting and inhibiting factors. This research was conducted through analytical techniques from the data that had been obtained during research activities and the researchers attempted to explain and explain rationally, objectively with the objectives and existing research problems. The method that the researcher uses in this research is a qualitative approach with the type of naturalistic phenomenological research, namely the type of research carried out by researchers to identify human experience about a certain phenomenon naturally. The implementation of the Problem posing method begins with doing absenteeism by students. Next, the educator forms a study group between 4-6 students in the group. After that, the teacher explains the material related to honest and fair behavior and avoids drinking, gambling, and fighting, then the teacher gives enough practice questions and the teacher asks students to ask questions 1 or 2 the questions are challenging and the students concerned must be able to solve them and randomly the educator asks students to present their findings in front of the class, in this case the teacher can determine students selectively based on the weight of the questions submitted by students after that the educator gives homework individually. The implementation of the problem posing method in increasing learning activities has supporting and inhibiting factors. The supporting factors are the ability of educators to apply the problem posing method, complete learning resources such as LKS books (Student Worksheets) and writing tools, the condition of students who are ready to learn. While the inhibiting factor is the limited time in the learning process. This problem posing method can be used as a learning method because learning activities carried out through the problem posing method can increase student learning activities.